A case report on leptospirosis with pseudohepatorenal syndrome (Indian Journal of Case Reports, 2022)
The spirochete Leptospira interrogans causes leptospirosis, a zoonosis. There are numerous clinical symptoms of leptospirosis. Clinical manifestations might range from a subclinical infection with a mild fever to severe clinical symptoms with jaundice and renal failure. Here, a case of leptospirosis with acute renal failure, thrombocytopenia, and hyperbilirubinemia is presented. A 51-year-old man presented with fever, body aches, muscle aches, colored urine, and jaundice for 2 days. On serology report, L. interrogans AB IGM-CARD was weekly positive. In the Renal function test, urea and creatinine values were high as well as the liver function test was abnormal. The patient was given 1 g of ceftriaxone intravenously and 100 mg of doxycycline orally. Hepatorenal treatment was supportive and the outcome was positive. It may have been overlooked when the diagnosis of leptospirosis was confirmed.